Self-Aligned Double and Quadruple Patterning Aware Grid Routing Methods - Kodama, Chikaaki; Ichikawa, Hirotaka; Nakayama, Koichi; Nakajima, Fumiharu; Nojima, Shigeki; Kotani, Toshiya; Ihara, Takeshi; Takahashi, Atsushi (IEEE transactions on computer-aided design of integrated circuits and systems, 2015)
Although self-aligned double and quadruple patterning (SADP, SAQP) have promising processes for sub-20 nm node advanced technologies and beyond, not all layouts are compatible with them. In advanced technologies, feasible wafer image should be generated effectively by utilizing SADP and SAQP where a wafer image is determined by a selected mandrel pattern. However, predicting a mandrel pattern is not easy since it is different from the wafer image (or target pattern). In this paper, we propose new routing methods for spacer-is-dielectric (SID)-type SADP, SID-type SAQP, and spacer-is-metal (SIM)-type SADP to generate a feasible layout satisfying the connection requirements. Routing algorithms comprising simple connecting and cutting rules are performed on a new grid structure where two (SID-type SADP) or three colors (SID-type SAQP and SIM-type SADP) are assigned alternately to grid-nodes. Then a mandrel pattern is selected without complex coloring or decomposition methods. Also, we try to reduce hotspots (potentially defective regions) by the proposed dummy pattern flipping for SID-type SADP. In experiments, feasible layouts meeting the connection requirements are generated and the effectiveness of the proposed framework is confirmed.